2015
DOI: 10.1016/j.enbuild.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The joint influence of albedo and insulation on roof performance: A modeling study

Abstract: a b s t r a c tThe advanced Princeton Roof Model (PROM) is evaluated and then applied to quantify the heat transferred through various modular roof structures over an entire year. The goal is to identify an optimal combination of roof reflectivity and insulation thickness that will reduce energy consumption and minimize cost. Meteorological data gathered over the Northeastern United States (Princeton, NJ) is used to force PROM. Our results reveal that for new constructions or for retrofits in the region, an R8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 33 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…Modifying roof albedo has been suggested extensively as a method to cool urban areas (e.g. Santamouris et al, 2011;Li et al, 2014;Ramamurthy et al, 2015). In the example, we conduct simulations from January 2012 to July 2012 with the first 6 months as the spin-up period.…”
Section: Impacts Of the Urban Area On Local Climatementioning
confidence: 99%
See 1 more Smart Citation
“…Modifying roof albedo has been suggested extensively as a method to cool urban areas (e.g. Santamouris et al, 2011;Li et al, 2014;Ramamurthy et al, 2015). In the example, we conduct simulations from January 2012 to July 2012 with the first 6 months as the spin-up period.…”
Section: Impacts Of the Urban Area On Local Climatementioning
confidence: 99%
“…to understand energy partitioning over urban surfaces (D. Sun et al, 2017;Wang et al, 2015;Ward and Grimmond, 2017;Zhao et al, 2014), pedestrian level meteorology to diagnose thermal comfort (Bar et al, 2011;Erell et al, 2013;Krayenhoff et al, 2018;Sun et al, 2016;Tan et al, 2009), or ambient radiation and wind conditions to assist building design (Chen, 2004;Jentsch et al, 2013;B. Li et al, 2015;Reinhart and Cerezo Davila, 2016;Santamouris et al, 2001). To obtain such information, accurate and agile modelling capacity of the urban weather and climate are essential.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible to combine several strategies in this regard. For example, several studies such as Brito and Santos [9], Ramamurthy et al [18], and Arumugam et al [19] found that in hot climates, roofs with combined thermal insulation and reflective coating is the best option. This combination could significantly reduce thermal insulation thickness and thus reduce the cost and maximise energy savings.…”
Section: Research Materials and Methodsmentioning
confidence: 99%
“…The insulation thickness increase was demonstrated to provide incremental benefits in energy savings which were reduced after a limit. Similarly, Ramamurthy et al [29,30] studied the joint influence of these two roof characteristics on building energy performance through a two-step experimental and numerical analysis. They highlighted the role of both albedo and insulation thickness for the reduction of the annual energy load attributable to the roof, and that wintertime penalties are negligible compared to summertime benefits with cool roofs.…”
Section: Introductionmentioning
confidence: 99%